Functional Study of desKR: A Lineage-Specific Two-Component System Positively Regulating Staphylococcus Aureus Biofilm Formation [Retraction] - Ma X; Wu Z; Li J; Yang Y (Infection and Drug Resistance)
Ma X, Wu Z, Li J, Yang Y. Infect Drug Resist. 2024;17:4037–4053. We, the Editor and Publisher of the journal Infection and Drug Resistance, are retracting the published article. Following publication, the authors raised concerns regarding the reproducibility of their work and requested the retraction of the article because they had lost confidence in the conclusions reported in the article. Further investigations by the Journal and Publisher identified additional concerns regarding the research methodology reported in the article. As these errors directly impact the reported results and conclusions, the authors, Editors and Publisher have agreed to retract the article to ensure correction of the scholarly record. We have been informed in our decision-making by our editorial policies and the COPE guidelines. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as ‘Retracted’.